Estimation of soil erosion using the Revised Universal Soil Loss Equation (RUSLE) in Relation to Landslides in Mid-hills of Nepal - Pathak, Lalit; Joshi, Kamana; Ghimire, Pradeep (Journal of Environment Sciences, 2023)
An attempt has been made in this research to assess soil erosion and its spatial distribution by the revised universal soil loss equation (RUSLE) model at Rangun Khola Watershed, western Nepal. The erosion factors were acquired from multiple sources (Satellite images, ALOSPALSAR DEM, SOTER soil database, Esri 2020 land cover map, rainfall database of DHM) and an integrated analysis was carried out in raster format of GIS. A landslide inventory was generated on the basis of satellite images and past literature to validate soil erosion intensity in the area. The result map of the RUSLE model was categorized into six levels based on the erosion severity, and 9.06 % of the area was found to be under extremely severe soil erosion risk (> 80 ton ha”1year”1) indicating urgent consequences. The frequency ratios for each level of potential erosion susceptible to landside exhibited a linear relationship depicting reasonable and satisfactory level of agreement between the landslide event/location data and the erosion map that validates the model result. The result of this study will be helpful to detect the sensitive zones presenting a priority of protection and offer valuable information that aids decision-makers and user agencies in creating adequate conservation planning programs to stop soil erosion and maintain the natural balance.